The cohesion protein ORD is required for homologue bias during meiotic recombination. - Webber, H.A.; Howard, L.; Bickel, S.E. (Journal of Cell Biology, 2004)
During meiosis, sister chromatid cohesion is required for normal levels of homologous recombination, although how cohesion regulates exchange is not understood. Null mutations in orientation disruptor (ord) ablate arm and centromeric cohesion during Drosophila meiosis and severely reduce homologous crossovers in mutant oocytes. We show that ORD protein localizes along oocyte chromosomes during the stages in which recombination occurs. Although synaptonemal complex (SC) components initially associate with synapsed homologues in ord mutants, their localization is severely disrupted during pachytene progression, and normal tripartite SC is not visible by electron microscopy. In ord germaria, meiotic double strand breaks appear and disappear with frequency and timing indistinguishable from wild type. However, Ring chromosome recovery is dramatically reduced in ord oocytes compared with wild type, which is consistent with the model that defects in meiotic cohesion remove the constraints that normally limit recombination between sisters. We conclude that ORD activity suppresses sister chromatid exchange and stimulates inter-homologue crossovers, thereby promoting homologue bias during meiotic recombination in Drosophila.